Assessment of Malaysian ICU Staff Perceptions Towards STAR Glycaemic Control Protocol - Razak A.A.; Abu-Samah A.; Razak N.N.; Baharudin S.; Suhaimi F.M.; Jamaludin U.K.; Ralib A.; Mat-Nor M.B.; Pretty C.G. (Institute of Electrical and Electronics Engineers Inc., 2023)
Intensive care units; Nursing; Stars; Stochastic systems; Surveying; Blood glucose management; Clinical feasibility; Control protocols; Critically-ill patients; Hyperglycaemia; Medical doctors; Model-based OPC; Staff perceptions; Surveys